2014
DOI: 10.1097/qai.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Programmatic Implications of Routine Viral Load Monitoring in Swaziland

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 12 publications
7
56
0
Order By: Relevance
“…To our knowledge, only one other study has reported on VL outcomes of a PMTCTB+ cohort in sub-Saharan Africa and reported similar findings [37]. VL monitoring was still quite a novel practice for health workers and its routine use for treatment monitoring was still not fully established [38]. In addition, according to our data, women were often lost to follow-up before they became eligible to receive their first VL at 6 months after ART initiation.…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, only one other study has reported on VL outcomes of a PMTCTB+ cohort in sub-Saharan Africa and reported similar findings [37]. VL monitoring was still quite a novel practice for health workers and its routine use for treatment monitoring was still not fully established [38]. In addition, according to our data, women were often lost to follow-up before they became eligible to receive their first VL at 6 months after ART initiation.…”
Section: Discussionmentioning
confidence: 89%
“…VL measured at 12 month intervals for 48 monthsNot statedNo time point specific provided for % patient with VL data available. Scheduled clinic visit 6 monthly at tertiary hospitalJanssen, 2010 [21]6–12 months447193/447 (43.2%)CD4%: 310/447 (69.3%); CD4: 315/447 (70.5%)NRLaboratory tests (CD4, VL, Hemoglobin/albumin) repeated 6 monthlyVL testing at referral hospital (75 km away); other tests at local hospitalJobanputra, 2014 [26]12 months55634767/5563 (86%)NRNRVL measured annually using a Generic HIV VL platform (Biocentric)VL testing at regional virology laboratoryMutevedzi, 2010 [20]12 months2527/3010758/2527 (30%)NRNRCD4 count and VL measured every 6 monthsVL testing at provincial labVL measured by Nucli-Sens Easy HIV-1 assay). Type of blood used not reportRich, 2012 [22]24 months926275/926 (29.7%)710/926 (76.7%)NRCD4 count measured 6 monthly using BD fluorescence-activated cell sorting count systemNot statedSelke, 2010 [14]12 monthsIntervention: 87Control: 102Intervention: 86/87 (99%)Control: 96/102 (94.1%)Intervention: 87/87 (100%)Control: 96/102 (94.1%)Intervention: 74/87 (85%)Control: 87/102 (85.3%)VL and CD4 count obtained at initial and close out research visit.…”
Section: Resultsmentioning
confidence: 99%
“…Observations from rural HIV clinics in various resource-limited countries have shown that inadequately managed HIV treatment and care programmes may result in high levels of virological failure and widespread drug resistance. 26,27 To date, only a few Tanzanian studies have investigated the virological effectiveness of ART and the emergence of HIV-DRM among ART-experienced HIV patients, typically under stavudine-based Ntamatungiro et al…”
Section: Discussionmentioning
confidence: 99%